Inovasi Guru Madrasah Ibtidaiyah dalam Pembelajaran di Era Pandemik Covid-19 - Taufiq Rohman (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to analyze and describe the innovations of Madrasah Ibtidaiyah teachers in learning in the Covid-19 pandemic era. This research was carried out at Madrasah Ibtidaiyah Negeri 1 Tasikmalaya City with the object of research being a high-class teacher. The research method used is a case study. The research data were analyzed using triangulation techniques. The results of his research include: 1) idea innovation is characterized by the implementation of an independent learning curriculum, Islamic religious madrasah, green school, mentally ready to continue education at a higher level. 2) method innovation is characterized by the application of blended learning models, and scientific learning methods. 3) media innovation is characterized by the use of information technology media in the learning process and learning evaluation.